Development of Small-Scale Hydro Energy Harvester using Piezoelectric Sensor - bin mohd azam, mohamad ariff; Sofian Mohd; Qamarul Ezani Kamarudin (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This project presents the development of a small-scale hydro energy harvester that utilizes piezoelectric technology to convert mechanical energy from water movement into electrical energy. The main objective is to explore a renewable energy solution suitable for powering low-energy devices, particularly in rural or off-grid areas where access to conventional electricity is limited. The energy harvester prototype was designed and fabricated using water-powered mechanisms to simulate different types of water motion, including artificial waves, flowing water, and falling water. A supporting circuit system was implemented to collect, rectify, and store the generated electrical energy. The system’s performance was evaluated based on the effectiveness of each water condition in generating electricity through mechanical interaction with the piezoelectric element. The results demonstrated that the type and intensity of water movement significantly influence the efficiency of energy harvesting. Among the tested scenarios, falling water showed the most promising performance due to the greater mechanical force exerted. This study confirms the feasibility of utilizing hydro-based piezoelectric systems for micro-energy harvesting applications. In conclusion, the developed prototype offers a practical and sustainable approach for generating renewable energy on a small scale. It holds potential for powering low-power electronic devices, environmental sensors, or Internet of Things (IoT) modules, contributing to the advancement of green energy technologies.